Legal Protection of Natural Resources and Environmental Justice in the Decentralization Era: Challenges and Solution in West Java - Acep Sumantri (International Forum of Researchers and Lecturers, 2026)
Subtheme 7: Environmental Law and Natural Resources. The management of natural resources and environmental protection in Indonesia faces complex challenges following the implementation of regional autonomy. While decentralization aims to bring governance closer to communities, it has also created gaps in legal protection, conflicts between economic interests and ecological sustainability, and unequal access to environmental justice for vulnerable groups. This study examines how legal frameworks currently regulate natural resource management, identifies barriers to fair and sustainable resource use, and proposes a legal model that balances regional authority, environmental preservation, and community rights. Using normative legal research supported by case studies on forest management, mineral extraction, and river basin governance in West Java Province, the analysis finds that overlapping regulations, weak enforcement of environmental rights, and marginalization of local communities hinder both resource sustainability and justice. The proposed approach strengthens legal standing for affected communities, establishes cross-jurisdictional resource management bodies, and embeds environmental justice principles into regional planning. This framework is expected to resolve conflicts, reduce environmental harm, and ensure that natural resources benefit present and future generations equitably.